Reliability study of motor controller in electric vehicle by the approach of fault tree analysis. (March 2021) - Shu, Xiong; Guo, Yingfu; Yang, Huan; zou, Hongxiang; Wei, Kexiang
Highlights: A detailed reliability study of the motor controller in pure electric vehicle by the approach of fault tree analysis. Among all modules of the motor controller, SMCs are more prone to failure than PCBs in each module of the motor controller. Control module is the most vulnerable at subsystem level, while SMCs of control module is the most unreliable at component level. The reliability of all motor controller components will degrade over time. The degradation is dominated mainly by control module rather than by IGBT and DC link capacitor. Abstract: Electric vehicles will be increasingly used in the coming years, but the reliability of them is still a matter of concern today. In order to address this issue, much work have been done by scholars to improve the reliability of motor controllers. However, motor controller is composed of multiple components. The structure, type, and characteristics of all these components may affect the reliability of the motor controller to different extent. But these issues have not been fully considered in previous research. In order to fill this gap of knowledge, the reliability of the motor controller, a vulnerable component in pure electric vehicle, is further studied in detail in this paper. Firstly, the fault tree of the motor controller is developed and then based on which, the failure rates of individual components in the motor controller are estimated based on the information given in the international standards. Finally, the tendency of the reliability index of the entire motor controller and its components against the service life of the electric vehicle is estimated. From the estimation results, not only the most vulnerable components in the motor controller are identified, but also the degradation of the entire motor controller over time is clearly observed. It is deemed that these new findings will be of great significance to the future reliability design and maintenance of pure electric. Additionally, the industry and interested reader can also have a deeper understanding of the reliability of electric vehicles.